Validation of vibration-based onboard asphalt density measuring system. - Minchin Jr., R. Edward
The nuclear density gauge served the industry well for almost forty years as project owners performed quality control on the asphalt paving and compaction process. recently, however, the responsibility for quality control of these processes has largely been given to the contractor. This shift in responsibility comes at a particularly unfavorable time for the average paving contractor. The construction industry is faced with the worst labor shortage in history, limiting the number of qualified quality control technicians and equipment operators. In addition, this is the dawn of the age of Superpave, a family of hot-mix asphalt mixes designed to combat pavement rutting by increasing the quantity of large aggregate in the mixes. Understandably, these are more difficult to compact. The Onboard Density Measuring System, a model patented by Penn State University, offers density measurements in real time at a rate of one per second during the compaction process, thereby affording the constructor the opportunity to recognize and correct compaction problems immediately while maintaining a permanent record of the entire process.
Keywords: Compaction; Asphalts; Construction